The multiple dimensions of bank complexity: Effects on credit risk-taking - Marinelli, Giuseppe; Nobili, Andrea; Palazzo, Francesco (Journal of Banking & Finance, 2022)
This paper examines the multi-dimensional concept of bank complexity and its relationship with credit risk for Italian banks using data at the bank-firm level. The different aspects of bank complexity are identified through the use of a factor analysis on a large set of bank-level variables. Bank complexity is well described by four factors: exposure to international commercial banking activities, geographic diffusion over the domestic territory, integration of market trading activities and fee income diversification. Our main result is that geographic diversification is associated to a decrease in the supply of lending to riskier firms; access to many local credit markets might provide banks with more chances to expand their loan supply by targeting safer borrowers. On the contrary, we document a positive relationship between banks’ fee income diversification and the amount of credit granted to riskier borrowers, but only when the latter hold multiple bank credit relationships. This evidence might point out that competition fosters banks’ risk-taking incentives on loan origination to sell additional financial services.